2012
DOI: 10.1111/j.1096-3642.2012.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Species delineation and global population structure of Critically Endangered sawfishes (Pristidae)

Abstract: Sawfishes are among the most endangered of all elasmobranch species, a factor fostering considerable worldwide interest in the conservation of these animals. However, conservation efforts have been hampered by the confusing taxonomy of the group and the poor state of knowledge about the family's geographical population structure. Based on historical taxonomy, external morphology, and mitochondrial DNA sequences (NADH-2), we show here that, globally, the sawfish comprise five species in two genera: Pristis pris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
145
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 62 publications
3
145
1
1
Order By: Relevance
“…Following Faria et al (2013), who included P. pristis from Peru based on previous works listing the species in Peruvian waters, subsequent scientific and technical publications also listed this species from Peru but without more precise distributional data and cited it as a historical distribution given the absence of confirmed records for more than 10 years. As a result, many researchers believed that the species had been extirpated from Peru (Carlson et al 2013a, Dulvy et al 2014, Harrison and Dulvy 2014.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…Following Faria et al (2013), who included P. pristis from Peru based on previous works listing the species in Peruvian waters, subsequent scientific and technical publications also listed this species from Peru but without more precise distributional data and cited it as a historical distribution given the absence of confirmed records for more than 10 years. As a result, many researchers believed that the species had been extirpated from Peru (Carlson et al 2013a, Dulvy et al 2014, Harrison and Dulvy 2014.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%
“…Pristis pristis is morphologically characterized by the first dorsal fin located in front of the origin of the pelvic fins, the presence, in all stages of growth, of the lower lobe of the caudal fin, and by having a shorter and wider rostrum than the other species of Pristis (Faria et al 2013). Recent studies have shown that P. perotteti from the Atlantic Ocean and P. microdon from the western Indo-Pacific Ocean are synonyms of P. pristis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are five extant species of sawfish, all of which possess an enlarged, tooth-lined rostrum (or "saw"), which has unfortunately been central to their widespread global decline, due to the saw rendering them extremely susceptible to net entanglement (Faria et al 2013;Dulvy et al 2014;Whitty et al 2014). Individuals may suffer mortality during entanglement or be euthanized or desawed prior to net removal for either operator safety or to simplify removal of the sawfish from the net.…”
mentioning
confidence: 99%